Insulin resistance in offspring of hypertensive parents. Issue 6896 (10th July 1993) - Beatty, O L; Harper, R; Sheridan, B; Atkinson, A B; Bell, P M
Abstract : OBJECTIVE–To determine if insulin resistance is present in normotensive adults at increased risk of developing hypertension. DESIGN–Normotensive subjects with at least one hypertensive parent were paired with offspring of normotensive parents (controls), being matched for age, sex, social class, and physical activity. SETTING–Outpatient clinic. SUBJECTS–30 paired subjects (16 men and 14 women) with and without a family history of hypertension, aged 18-32, with a body mass index < 25 kg/m2, with blood pressure < 130/85 mm Hg, and not taking drugs. INTERVENTIONS–Euglycaemic glucose clamp (two hour infusion of insulin 1 mU/kg/min) and intravenous glucose tolerance test (injection of 100 ml 20% glucose). MAIN OUTCOME MEASURES–Insulin mediated glucose disposal and insulin secretion. RESULTS–The offspring of hypertensive parents had slightly higher blood pressure than did the controls (mean 117 (SD 6) v 108 (5) mm Hg systolic, p = 0.013; 76 (7) v 67 (6) mm Hg diastolic, p = 0.017). Their insulin mediated glucose disposal was lower than that of controls (29.5 (6.5) v 40.1 (8.6) mumol/kg/min, p = 0.002), but, after adjustment for blood pressure, the difference was not significant (difference 6.9 (95% confidence interval -1.5 to 15.3), p = 0.10). Insulin secretion in the first hour after injection of glucose was slightly but not significantly higher in the offspring of hypertensive patients (9320 (5484) v 6723 (3751) pmol.min/l). The two groups had similar concentrations of plasma glucose (5.2 (0.3) v 5.1 (0.4) mmol/l), serum cholesterol (4.4 (0.8) v 4.6 (0.8) mmol/l), serum triglyceride (0.89 (0.52) v 0.68 (0.27) mmol/l), and serum low density lipoprotein cholesterol (2.81 (0.65) v 2.79 (0.61) mmol/l). The offspring of hypertensive parents, however, had lower serum concentrations of high density lipoprotein cholesterol (1.24 (0.31) v 1.56 (0.35) mmol/l, p = 0.002) and higher serum concentrations of non-esterified fatty acids (0.7 (0.4) v 0.4 (0.4) mmol/l, p = 0.039). CONCLUSIONS–Young normotensive subjects who are at increased risk of developing hypertension are insulin resistant.